Hubungan Asupan Makanan dengan Tingkat Prestasi Anak Sekolah Menengah Atas - Latifah, Ifa; Darussalam, Husni Esa; Anastasia, Rizka; Artati, Ratna Dewi; Darma, Sidrah (Innovative: Journal Of Social Science Research, 2024)
High school students are usually between 15 and 18 years old. The results of by the OECD in 2018 showed that the literacy, mathematics and science abilities of 15 year old students in Indonesia were ranked 71st out of 78 countries. Students are in an important phase of development, both physically and cognitively, which makes good food intake especially important. This research using a literature review  method using Google Scholarand the National Center for Biotechnology Information (NCBI). Based on this research it was found that adequate balanced food intake has an influence on school children's achievement. Teenagers who eat breakfast regularly have better academic performance compared to those who don't eat breakfast. Breakfast contributes to improved attention, memory and problem-solving abilities. Studies show that a balanced breakfast can improve cognitive function which is important for academic performance as well as better mental health. Students who eat breakfast tend to have lower stress levels and higher emotional well-being. From this research, can be concluded that a significant relationship between food intake and the achievement level of high school and upper school children.